STUDENT AND TEACHER PERCEPTION ANALYSIS ON GUIDANCE AND COUNSELLING AT SMA NEGERI 10 MEDAN - Susnesi Girsang; Erikson Saragih (Universitas Negeri Medan, 2020)
Abstract: Analysis of Teacher and Student Perception on Guidance and Counseling Service at SMA Negeri 10 Medan. This study aims to describe the Perceptions of Teachers and Students of Guidance and Counseling Services in SMA Negeri 10 Medan. The research design is descriptive survey research. The sample of this study were 50 teachers and 50 students who were selected using random sampling techniques. The instrument of data collection in this study was a questionnaire using a Likert scale which was first validated by experts, reviews and discussions. This research uses quantitative data analysis methods. Data analysis was performed using descriptive statistical measurements such as, percentage, average, standard division, and independent t-test calculated to analyze responses from students, and teachers. The results of this study indicate the perception score for guidance and counseling needs for student learning is positive. Students and teacher's perception of school guidance and counseling services is very influential on the formation of student behavior, personal problems and student empowerment and decision making is negative. The t-test results showed that there were no statistically significant differences between students and teachers on the perception scores of guidance and counseling services which meant that both teachers and students had the same perception for guidance and counseling services in their schools. Students 'perceptions of the professionalism of supervisors are in the sufficient category, while teachers' perceptions are negative. Regarding the cost effectiveness of both student guidance and counseling services and teacher perceptions mean negative scores. From these results it is recommended that since students and teachers' perceptions can be affected based on sustained guidance and counseling; Education bureaus in collaboration with tertiary institutions must prepare vocational training to improve the skills of counseling and counseling officers.Keywords: Perception, Guidance; Counseling; Teacher; StudentAbstrak: Analisis Persepsi Guru Dan Siswa terhadap Layanan Bimbingan Konseling Di Sma Negeri 10 Medan. Penelitian ini bertujuan untuk mendeskripsikan Persepsi Guru dan Siswa terhadap Layanan Bimbingan dan Konseling di SMA Negeri 10 Medan. Desain penelitian adalah penelitian survei deskriptif. Sampel penelitian ini adalah 50 guru dan 50 siswa yang dipilih dengan menggunakan teknik random sampling. Instrumen pengumpulan data penelitian ini adalah kuesioner dengan menggunakan skala Likert yang terlebih dahulu divalidasi oleh para ahli, ulasan dan diskusi. Penelitian ini menggunakan metode analisis data kuantitatif. Analisis data dilakukan dengan menggunakan pengukuran statistik deskriptif seperti, persentase, rata-rata, pembagian standar, dan t-test independen dihitung untuk menganalisis respon dari siswa, dan guru. Hasil dari penelitian inimenunjukkan skor persepsi untuk kebutuhan bimbingan dan konseling untuk siswa belajar adalah positif. Persepsi siswa dan guru terhadap bimbingan sekolah dan layanan konseling sangat berpengaruh terhadap pembentukan perilaku siswa, masalah pribadi dan siswa pemberdayaan dan pengambilan keputusan adalah negatif. Hasil uji-t menunjukkan bahwa tidak ada perbedaan yang signifikan secara statistik antara siswa dan guru terhadap skor persepsi layanan bimbingan dan konseling yang berarti bahwa baik guru maupun siswa memiliki persepsi yang sama untuk layanan bimbingan dan konseling di sekolah mereka. Persepsi siswa terhadap profesionalitas petugas pembimbing adalah dalam kategori cukup, sedangkan persepsi guru negatif. Mengenai efektivitas biaya layanan bimbingan dan konseling kedua siswa dan persepsi guru berarti skor negatif. Dari hasil ini direkomendasikan bahwa Sejak persepsi siswa dan guru dapat terpengaruh berdasarkan bimbingan dan konseling yang bertahan; Biro pendidikan bekerja sama dengan lembaga pendidikan tinggi harus mempersiapkan pelatihan kerja untuk meningkatkan keterampilan bimbingan dan petugas konseling.Kata kunci: Persepsi, Bimbingan; Konseling; Guru; Siswa